2023
DOI: 10.3389/fcell.2023.1199440
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of gender and age on meibomian gland in aged people using artificial intelligence

Abstract: Purpose: To evaluate the effects of age and gender on meibomian gland (MG) parameters and the associations among MG parameters in aged people using a deep-learning based artificial intelligence (AI).Methods: A total of 119 subjects aged ≥60 were enrolled. Subjects completed an ocular surface disease index (OSDI) questionnaire, received ocular surface examinations including Meibography images captured by Keratograph 5M, diagnosis of meibomian gland dysfunction (MGD) and assessment of lid margin and meibum. Imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Eyelid margin irregularity could be found in severe states of MGD and EDE and in elderly populations [30,31]. Due to the small sample analysed in the present study, only 3 meibum samples were from subjects that showed eyelid margin irregularity (group 2), against 15 samples of healthy ones.…”
Section: Discussionmentioning
confidence: 70%
“…Eyelid margin irregularity could be found in severe states of MGD and EDE and in elderly populations [30,31]. Due to the small sample analysed in the present study, only 3 meibum samples were from subjects that showed eyelid margin irregularity (group 2), against 15 samples of healthy ones.…”
Section: Discussionmentioning
confidence: 70%